The concept genesis of the ethical doctrines of kiev academists - I. V. Kondratyeva, (Ukrainian Cultural Studies, 2018)
The article reveals the reasons for the Kyiv thinkers to emphasize their ethical issues in their creative intelligence. Most of all there was need for justification in the light of the moral postulates of metaphysical epistemological and eschatological developments, an updated tendency towards the injection of ethics in philosophical concepts which is characteristic to the development of European thought of the second half of the nineteenth century, needs of social practice, distribution of nihilistic ideas in society. The process of forming the ethical academic doctrine cannot be conceived without solving the problem of ideological influences. The following processes are recognized by: a) Mainly but not exclusively the Eastern-Byzantine tradition which was a logical extension of holy teachings; b) Influence of Kant's moral philosophy and in part Fichte's and theist-oriented theories of German thinkers of the nineteenth century. The ideas of the moral-educational character contained in the works of the holy fathers and teachers of the church, in particular Athanasius the Great, John Chrysostom, John Climacus, Ambrose of Mediolans, who are subsequently influenced the formation of the ethical doctrine of the Kyiv thinkers. The ideological discrepancy between spiritual philosophers and their predecessors - professors of the Kyiv-Mohyla Academy, who came out in their intelligence from the provisions of Aristotelian ethics, is emphasized. Reasons of the influence of German idealism were found in particular practical philosophy on the process of formation of ethical attitudes of Kyiv academicians. Separately the most influential researchers of the idea of the moral philosophy of Kant and the principle of morality a priori are considered. In order to identify possible recipes of theistic concepts of German thinkers the main propositions of the theologies of morality explained by A. Richel, F. Schleiermacher, H. Martensen, A. Wutke, R. Root, A. Ettingen, K. Palmer. Actually the ethical doctrine of the thinkers of the Kiev Theological Academy is actualized on the one hand through the creative processing of the ideological achievements of patristics, on the other hand the concepts of the practical philosophy of German idealism.
Keywords: theistic ethics, moral philosophy, morality, theological virtues, moral ideal, good